THE EFFECT OF STORE ATMOSPHERES ON CONSUMER PURCHASE DECISION ON RE-MART RETAIL IN PALEMBANG CITY - unpal, zubaida (Jurnal Manajemen, 2019)
This study aims to determine the influence of store atmosphere (Store Atmosphere) which consists of variable Store exterior, General interior, Store layout, and Interior display to consumer purchasing decision at Rie Mart Retail in Palembang City. This study uses quantitative approach with the number of samples of 100 people determined by using the technique of Accidental Sampling. The results can be seen that the variables of Store Exterior, General Interior, Store Layout and Interior Display together have a significant positive effect on purchasing decisions Based on multiple regression equation it can be seen that the General Interior variable has the greatest influence with the coefficient value of 0.153. From the results of multiple regression seen coefficient of determination (R square) of 0.55 or 55%. This means that Store Exterior, General Interior, Store Layout and Interior Display can explain the variation of purchasing decision 55%, while the remaining 45% explained by other variables outside this research.